TEMPORAL PLANKTON COMMUNITY STRUCTURE (PCSM) FOR AQUACULTURE PLANNING IN UNMANAGED PONDS - ROY, K. (Journal of the Inland Fisheries Society of India, 2021)
The study deals with development of a tool called PCSM, which can aid region specific, eco-based and climate change resilient aquaculture planning in unmanaged ponds. Based on the monthly distribution of phytoplankton and zooplankton groups, temporal variations in the annual plankton community structure were mapped for urban and rural ponds of Raipur, Chhattisgarh. The maps were created in SigmaPlot v11.0. The maps consisted of multiple spline curves with 5% scientific padding. The applicability of PCSM includes: timing the release of fish seeds just before the burst phase of the preferred plankton groups; implementation of fertilization programme as the burst phase starts to drop for sustaining preferred plankton groups for longer duration; and harvesting during the lag phases. The limitations of PCSM includes: applicable to small closed water bodies like ponds where plankton dynamics is predictable; region specific; and it is more applicable in the planning of ’modified-extensive aquaculture’ which depends exclusively on plankton. Observations and recommendations based on PCSM are discussed in this paper for ponds of the region. Key words: PCSM, aquaculture planning, modified extensive aquaculture, unmanaged ponds, Chhattisgarh